Cirkulär näringsåtervinning: Kväve och fosfor från avloppsvatten till fiskfoder genom mikroalger och bakterier - ALKHATIB, Ammar; EMANUELSSON, Matilda; LUNDIN, Jacob; MEDBLOM, Oscar; OPPERUD, Martin; TROFAST, Klara (My University, 2025)
This thesis examines the implementation of fish feed production through growth of bacterial and micro algal biomass with nutrients from wastewater at a treatment facility. In order to investigate this, a study with supporting calculations was con ducted to determine the energy and land usage necessary for the introduction of such a production processes. This was achieved through analysing relevant articles and studies. Furthermore the study examines the optimal point in a wastewater tre atment facility at which such a production process should be implemented. This was done by experimentally determining which form of nitrogen bacteria and microalgae prefer for optimal growth. The results of this study show that the application of bacterial growth using nutrients from wastewater is significantly more efficient in terms of land and energy use. The experimental results show that this type of system should be implemented after the nitrification step in the wastewater treatment process to ensure optimal bacterial growth. The findings of the study highlight the future potential of using bacterial biomass for fish feed production. Its low energy and land requirements make implementation of bacterial biomass production a relevant focus for future research in recycling of wastewater nutrients.
Keywords: Wastewater treatment; Fish feed; Microalgae cultivation; Bacteria cultivation